Design optimization of PM couplings using hybrid Particle Swarm Optimization-Simplex Method (PSO-SM) Algorithm - El-Wakeel, Amged S. (Electric power systems research, 2014)
•A PSO-SM optimization technique has been proposed to optimize the design of the PM coupling drive.•The coupling performance is predicted using a layer model approach that compared with FEA for validation.•The proposed PSO-SM technique is compared to other published techniques like PSO, and GA-SM.•The simulation showed that the proposed algorithm (PSO-SM) is the most efficient one. The aim of this paper is to explore the use of the proposed hybrid Particle Swarm Optimization-Simplex Method (PSO-SM) algorithm to optimize the design of PM couplings subject to several key design constraints. The proposed hybrid optimization algorithm is constructed based on combining two well-known optimization techniques: Particle Swarm Optimization (PSO) and Simplex Method (SM). The PSO has obvious capabilities in global search while the SM has exceptional advantages in local search. As a hybrid algorithm, the PSO-SM has the outstanding feature of combining the ability of global searching and local canvassing. On the other hand, Permanent Magnet (PM) drive couplings are used in power transmission in a wide range of industrial applications. A standard coupling design is used as a good starting point for the conventional Simplex Method and to define the performance constraints for the proposed hybrid optimization algorithm. New coupling designs are developed and optimized to demonstrate the superior capabilities of PSO-SM algorithm as a global optimization technique.